Cultural identity in America. (Australia ; Boston, MA : Wadsworth, 2013)
Discusses issues surrounding identity and culture in the United States in the 21st century.
Keywords: Group identity -- United States -- 21st century; Social classes -- United States; United States -- Social conditions -- 21st century